Lifestyle changes during the first and second waves of the COVID-19 pandemic in medical college students: are there gender-related differences? - Coppi, Francesca; Nasi, Milena; Sabatini, Silvia; Bellini, Pierantonio; Generali, Luigi; Mecugni, Daniela; Farinetti, Alberto; Consolo, Ugo; Mattioli, Anna Vittoria (Acta Biomedica Atenei Parmensis, 2022)
Background and aims. The COVID-19 pandemic has seriously affected young people. The present study aims to explore the effects of COVID-19 on lifestyle in 500 undergraduate students both during the acute phase of the pandemic (so-called "first wave") and during the second spread of infections (so-called "second wave"). Gender differences were also explored. Methods and results. During the first wave we found weight gain in 48.6% of subjects, a switch to an unhealthy diet (43%), and an increase in the amount of food introduced (35%). Interestingly, women showed higher intake of food in order to cope, while men privileged higher wine consumption as a coping mechanism. We observed a sharp reduction in physical activity, increased sedentary behaviours and deterioration in sleep quality. Stress correlates with eating to cope (r=0.86; p